Primary Sjögren's syndrome: new clinical and therapeutic concepts. Issue 3 (21st October 2004) - Ramos-Casals, M; Tzioufas, A G; Font, J
Abstract : Sicca features are the central clinical manifestations of Sjögren's syndrome (SS), but recent studies have confirmed that primary SS has a systemic expression, including extraglandular manifestations. Patients with a predominantly extraepithelial expression should be managed differently from patients with predominantly periepithelial or sicca limited disease. In coming years treatment will be based on muscarinic agonists for sicca features and immunosuppressive/biological agents for extraglandular features.